Generation of tunable multi-wavelength EDFL by using graphene thin film as nonlinear medium and stabilizer - Ahmad, Harith; Hassan, N.A.; Aidit, S.N.; Tiu, Zian Cheak (Elsevier, 2016)
The applications of graphene thin film as a nonlinear medium and stabilizer to generate a stable multi-wavelength is proposed and demonstrated. A 50 m long highly nonlinear photonic crystal fiber (PCF) is incorporated into the cavity to achieve unstable multi-wavelength based on nonlinear polarization rotation (NPR) effect. By introducing the graphene thin film into the cavity, a stable multi-wavelength oscillation is obtained. The laser generates more than 7 lasings with constant spacing of 0.47 nm. The output is highly stable with power fluctuation of less than 3 dB within a period of 30 min. The multi-wavelength EDFL exhibits a tunability from the center wavelength of 1550 nm to 1560 nm.